Nano-Dynamic Mechanical Analysis (nano-DMA)ofCreep BehaviorofShales: Bakken case study - Liu K, Ostadhassan M, Bubach B, Dietrich R, Rasouli V. (Journal of Materials Science, 2018)
Understanding the time-dependent mechanical behavior of rocks is important from various aspects and different scales such as predicting reservoir subsidence due to depletion or proppant embedment. Instead of using the conventional creep tests, nano-dynamic mechanical analysis (nano-DMA) was applied in this study to quantify the displacement and mechanical changes in shale samples over its creep time at a very fine scale. The results showed that the minerals with various mechanical properties exhibit different creep behavior. It was found that under the same constant load and time conditions, the creep displacement of hard minerals would be smaller than those that are softer. On the contrary, the changes in mechanical properties (storage modulus, loss modulus, complex modulus and hardness) of hard minerals are larger than soft minerals. The results from curve fitting showed that the changes in creep displacement, storage modulus, complex modulus and hardness over creep time follow a logarithmic function. We further analyzed the mechanical changes in every single phase during the creep time based on the deconvolution method to realize each phase’s response independently. Two distinct mechanical phases can be derived from the deconvolution histograms. As the creep time increases, the volume percentage of the hard mechanical phase decreases, while this shows an increase for soft phases. The results suggest that nano-DMA can be a strong advocate to study the creep behavior of rocks with complex mineralogy.